Solving method for stability problem of elasto plastic cylindrical shells with compressible material subjected to complex loading processes - Dung, Dao Van (Vietnam Journal of Mechanics, 2001)
The system of stability equations of elasto plastic cylindrical shell made of compressible material was established in work [3]. In the present paper, we study the solution of the problems and methods for determining the critical load. The obtained results describe the influence of the compressibility of material on the stability of the shell. When a material is incompressible, these results red.uce to the previous well-known ones (see [1, 2, 4, 5]).